1995
DOI: 10.1111/j.1750-3639.1995.tb00625.x
|View full text |Cite
|
Sign up to set email alerts
|

Neuropathological Diagnostic Criteria for Creutzfeldt‐Jakob Disease (CJD) and Other Human Spongiform Encephalopathies (Prion Diseases)

Abstract: Neuropathological diagnostic criteria for Creutzfeldt-Jakob disease (CJD) and other human transmissible spongiform encephalopathies (prion diseases) are proposed for the following disease entities: CJD--sporadic, iatrogenic (recognised risk) or familial (same disease in 1st degree relative): spongiform encephalopathy in cerebral and/or cerebellar cortex and/or subcortical grey matter; or encephalopathy with prion protein (PrP) immunoreactivity (plaque and/or diffuse synaptic and/or patchy/perivacuolar types). … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
277
1
13

Year Published

1998
1998
2016
2016

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 379 publications
(295 citation statements)
references
References 29 publications
4
277
1
13
Order By: Relevance
“…One might expect that the disease-associated PrPres would be capable of stimulating glial cells as deposition of PrPres is usually colocalized with gliosis (10,(43)(44)(45). Furthermore, various in vitro studies have demonstrated microglial activation by the neurotoxic fibrillar form of PrP peptide 106 -126 (14 -17).…”
Section: Discussionmentioning
confidence: 99%
“…One might expect that the disease-associated PrPres would be capable of stimulating glial cells as deposition of PrPres is usually colocalized with gliosis (10,(43)(44)(45). Furthermore, various in vitro studies have demonstrated microglial activation by the neurotoxic fibrillar form of PrP peptide 106 -126 (14 -17).…”
Section: Discussionmentioning
confidence: 99%
“…It causes a rapidly progressive neurodegeneration, ultimately leading to the patient's death within months to few years [27]. To date, a definite diagnosis can only be made by neuropathological examination of brain tissue with immunochemical demonstration of the pathogenic isoform of the prion protein (PrP Sc ) [4]. Clinically, the diagnosis of possible sCJD is made based on neurological findings of rapidly progressive dementia (less than 2 years duration) together with at least two of the following symptoms: myoclonus, ataxia, pyramidal or extrapyramidal signs, akinetic mutism, visual and psychiatric disturbances [26].…”
Section: Introductionmentioning
confidence: 99%
“…4 Definite diagnosis of sCJD requires neuropathological or immunochemical detection of the prion protein (PrP-CJD) in brain tissue. 5 PrP-CJD arises through the post-translational conformational conversion of the normal endogenous PrP (PrPC or PrPSen) and accumulates preferentially in nervous tissue. PrP-CJD is also the main component of the infectious CJD agent and propagates itself by seeding or templating the assembly of PrPC into misfolded multimers that can take the form of amyloid fibrils.…”
Section: Discussionmentioning
confidence: 99%